God's love story : past, present and future in the Deuteronomistic composition - Galil, Gershon (Zaphon Verlag, 2022)
"Gershon Galil's study examines the formation of the books included in the'Deuteronomistic Composition', and the historical and theological perceptions of the Deuteronomist (Dtr), who composed the'Deuteronomistic Composition'during the Babylonia exile, and completed it ca. 560 BCE. According to the author, the'Deuteronomistic Composition'included not only the books of Deuteronomy, Joshua-Kings, but the book of Jeremiah as well. Deuteronomy is the preface to this composition, and Jeremiah seals it; in Deuteronomy the path is demarcated and the norms are fixed; the body of the composition, namely the books from Joshua to Kings, presents a detailed history of the relation between God and Israel, from the conquest of the good land to the destruction of the Temple and the loss of the land. The book of Jeremiah, which concludes the composition, discusses at length the decline and fall of Judah, analyzes the sins that brought about the destruction, and at the same time propagates the gospel of redemption among the exiles. Like Moses, who predicts exile but also redemption, Jeremiah is the prophet of destruction but also of redemption. So Dtr examines the past according to the principles of the'Torah of Moses'(Deuteronomy) - and delineates the future in light of God's word in the mouth of His prophets - primarily Moses and Jeremiah. God's eternal love for Israel is the main tenet of Dtr's worldview. In his opinion, the bond between the Lord and Israel is endless. Its beginning is in the days of the Patriarchs but it will never end. As the relationship is everlasting, the nation of Israel is divine by nature: eternal and holy. The circular nature of the relationship between God and His people implies, in essence, a reality of closeness and distance, affection and anger, sin and repentance, punishment and salvation. Fulfillment of the word of God is one of the central motifs of the'Deuteronomistic Composition'. Since the main message of Dtr is that God promises Israel a return to the land, eternal love and an everlasting covenant, the people may wonder whether God's promises can be trusted. The answer comes in many scriptures that emphasize the fulfillment of the word of God and teach that God's promises can always be trusted."--Publisher
Keywords: Bible. -- Old Testament -- History of Biblical events.; Bible. -- Old Testament -- Language, style.; Bible. -- Jeremiah -- Criticism, interpretation, etc.; D document (Biblical criticism); RELIGION / Biblical Criticism & Interpretation / Old Testament